Defund the police : an international insurrection / Chris Cunneen. - Cunneen, Chris, 1953- (Policy Press, 2023)
This book examines the 'defund the police' movement from historical and contemporary perspectives. Against the backdrop of abolition and the failure of police reform, it uses international case studies to reimagine community safety beyond policing and imprisonment.